Advancing Amphibian Conservation through Citizen Science in Urban Municipalities - Tracy S. Lee; Nicole L. Kahal; Holly L. Kinas; Lea A. Randall; Tyne M. Baker; Vanessa A. Carney; Kris Kendell; Ken Sanderson; Danah Duke (Diversity, 2021)
As cities adopt mandates to protect, maintain and restore urban biodiversity, the need for urban ecology studies grows. Species-specific information on the effects of urbanization is often a limiting factor in designing and implementing effective biodiversity strategies. In suburban and exurban areas, amphibians play an important social-ecological role between people and their environment and contribute to ecosystem health. Amphibians are vulnerable to threats and imbalances in the aquatic and terrestrial environment due to a biphasic lifestyle, making them excellent indicators of local environmental health. We developed a citizen science program to systematically monitor amphibians in a large city in Alberta, Canada, where 90% of pre-settlement wetlands have been removed and human activities continue to degrade, alter, and/or fragment remaining amphibian habitats. We demonstrate successes and challenges of using publicly collected data in biodiversity monitoring. Through amphibian monitoring, we show how a citizen science program improved ecological knowledge, engaged the public in urban biodiversity monitoring and improved urban design and planning for biodiversity. We outline lessons learned to inform citizen science program design, including the importance of early engagement of decision makers, quality control assessment, assessing tensions in program design for data and public engagement goals, and incorporating conservation messaging into programming.